Mass spectrometry in structural proteomics: study of viral protein complexes - Ravi, Anirudhan (Jihočeská univerzita, 2022)
This thesis investigated the avian reovirus sigma NS protein and its interaction with RNA using mass spectrometric methods. The sigma NS structure is still not known; thus, hydrogen-deuterium exchange and cross-linking coupled to mass spectrometry were employed to understand protein conformation. This research provides insights into protein-RNA interactions and the obtained data will be used in future work to predict protein structure.
Mass spectrometry in structural proteomics: study of viral protein complexes
Keywords: Avian reovirus; sigma NS protein; 3D structure; matrix-assisted laser/desorption ionization; hydrogen-deuterium exchange; cross-linking mass spectrometry.; Avian reovirus; sigma NS protein; 3D structure; matrix-assisted laser/desorption ionization; hydrogen-deuterium exchange; cross-linking mass spectrometry.